Research Progress on the Efficacy and Safety of Spironolactone in Reversing Left Ventricular Hypertrophy in Hemodialysis Patients - Sun Z; Chen Z; Liu R; Lu G; Li Z; Sun Y (Dove Medical Press, 2023)
Zuoya Sun,1 Zhiyuan Chen,1 Ruihong Liu,1 Gang Lu,1 Zhuo Li,1 Yi Sun2 1Department of Family Medicine, the University of Hong Kong-Shenzhen Hospital, Shenzhen, People's Republic of China; 2Department of Nephrology, Beijing Huairou Hospital, Beijing, People's Republic of ChinaCorrespondence: Yi Sun, Department of Nephrology, Beijing Huairou Hospital, No. 9 Yongtai North Street, Huairou District, Beijing, 101400, People's Republic of China, Tel +86-010-69644822, Fax +86-010-69622761, Email Sunyihuairou@163.comAbstract: The mineralocorticoid receptor antagonist spironolactone has been shown to improve cardiac function and reverse left ventricular hypertrophy in heart failure patients, but there are no consistent findings on the efficacy and safety in hemodialysis patients. Abnormal aldosterone secretion plays a critical role in the formation of left ventricular hypertrophy. Because of the existence of "aldosterone escape", the routine use of angiotensin-converting enzyme inhibitors/angiotensin receptor blockers does not completely inhibit aldosterone secretion. Low-dose spironolactone (25 mg/d) has been found in small-sample clinical studies to have a significant positive impact with respect to decreasing left ventricular mass index, increasing left ventricular ejection fraction, reversing left ventricular hypertrophy, and improving cardiovascular function while still being safe. More prospective multicenter clinical trials with large sample sizes are needed, however, to provide convincing evidence.Keywords: spironolactone, hemodialysis, left ventricular hypertrophy, LVH, mineralocorticoid receptor antagonists, MRA, hyperkalemia